LA TÉCNICA DE LA REMINISCENCIA VERBAL EN EL EPISODIO DE ARIADNA DEL POEMA LXIV DE CATULO - Ruiz Sánchez, Marcos (Myrtia, 1995)
The present study aims to analyze the technique of verbal reminiscences, repeated throughout the poem LXIV, above all in Ariadne's episode, together with the implications these verbal echoes have for the meaning of the text. Catullus' poem LXIV was undoubtedly conceived by the author himself as his masterpiece and it reveals the meticulousness with the neoteric poets composed their works of greatest poetic zeal. This explains the compositional virtuosity that can frequently be discovered in the text. The procedure serves to provide a framework for the descriptive sections or direct speech; to link the differente events by urderlining the casual relations between them and to confer a symbolic nature on the text.